2000
DOI: 10.1023/a:1017546601065
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Astyanax scabripinnis has been considered a species complex because it presents high karyotypic and morphological variability among its populations. In this work, individuals of two A. scabripinnis populations from different streams in the same hydrographic basin were analyzed through C-banding and AgNOR. Although they present distinct diploid numbers, they show meta and submetacentric chromosome groups highly conserved (numerically and morphologically). Other chromosomal characteristics are also shared by bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
14
0
4

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(23 citation statements)
references
References 27 publications
5
14
0
4
Order By: Relevance
“…Although there are different patterns of heterochromatin in A. scabripinis and A. fasciatus, the pattern of centromeric heterochromatin verified here in A. paranae was also observed by some authors in A. scabripinnis (Stange & Almeida-Toledo 1993; Souza et al 1996;Mantovani et al 2000;Vicari et al 2008). In A. fasciatus, the presence of telomeric heterochromatin verified in the present study was also observed by other authors (Daniel-Silva & Almeida Toledo 2001;Centofante et al 2003;Pazza et al 2008).…”
Section: Discussionsupporting
confidence: 88%
“…Although there are different patterns of heterochromatin in A. scabripinis and A. fasciatus, the pattern of centromeric heterochromatin verified here in A. paranae was also observed by some authors in A. scabripinnis (Stange & Almeida-Toledo 1993; Souza et al 1996;Mantovani et al 2000;Vicari et al 2008). In A. fasciatus, the presence of telomeric heterochromatin verified in the present study was also observed by other authors (Daniel-Silva & Almeida Toledo 2001;Centofante et al 2003;Pazza et al 2008).…”
Section: Discussionsupporting
confidence: 88%
“…Differences in the amount or distribution of heterochromatin identified by C-banding are considered important for some fish groups and the distribution of C-bands may characterize genera, species and populations (Montovani et al , 2000). …”
Section: Discussionmentioning
confidence: 99%
“…In the Jordão River population, chromosome pair 2 was smaller than the same pair in the Pântano and Feijão Streams populations (Figure 1). Variations in diploid number were observed between populations of species from the A. scabripinnis and A. fasciatus complexes and resulted from chromosome translocations (Mantovani et al , 2000; Artoni et al , 2006; Vicari et al , 2008a). Nevertheless, A. altiparanae exhibited a conserved 2n = 50 chromosomes in all the populations karyotyped (Table 1).…”
mentioning
confidence: 99%